Quantitative intrinsic auto-cathodoluminescence can resolve spectral signatures of tissue-isolated collagen extracellular matrix - Zielinski, Marcin S.; Vardar, Elif; Vythilingam, Ganesh; Engelhardt, Eva-Maria; Hubbell, Jeffrey A.; Frey, Peter; Larsson, Hans M. (Nature Research, 2019)
By analyzing isolated collagen gel samples, we demonstrated in situ detection of spectrally deconvoluted auto-cathodoluminescence signatures of specific molecular content with precise spatial localization over a maximum field of view of 300 µm. Correlation of the secondary electron and the hyperspectral images proved ~40 nm resolution in the optical channel, obtained due to a short carrier diffusion length, suppressed by fibril dimensions and poor electrical conductivity specific to their organic composition. By correlating spectrally analyzed auto-cathodoluminescence with mass spectroscopy data, we differentiated spectral signatures of two extracellular matrices, namely human fibrin complex and rat tail collagen isolate, and uncovered differences in protein distributions of isolated extracellular matrix networks of heterogeneous populations. Furthermore, we demonstrated that cathodoluminescence can monitor the progress of a human cell-mediated remodeling process, where human collagenous matrix was deposited within a rat collagenous matrix. The revealed change of the heterogeneous biological composition was confirmed by mass spectroscopy.